Imaginary Geographies of Classic and New Travel Media – Reality-Construction of Touristic Intermediaries with Sevilla as a Case in Point - Tatjana Thimm (Via@)
The theoretical approach of “Imaginary Geographies” by Christoph Hennig serves as a framework for the examination of forms of reality construction via classical and new travel media. Here the questions in which way these selected intermediaries form part of the construction process, what are similarities and differences to be observed and which models can be designed upon this basis, shall be answered. Seville, a destination exposed to image forming imaginary geographies for a longer time, serves as a case study.